Issues of LNG producing companies entering the eastern markets and ways to overcome them - F. A. Ostroumov; V. Ya. Afanasiev (Вестник университета, 2024)
This article is  devoted to  identifying the features of   the  еastern liquefied natural gas (hereinafter referred to   as LNG) markets and new opportunities for entering them. The purpose of   this article is  to study the problems of   LNG producing companies entering the еastern markets and ways to   overcome them. The work analyses the current state of   the  еastern LNG markets and their development prospects,   existing barriers, including those caused by  the conflict in   the Middle East, and possible consequences of   the escalation of   the conflict. The authors consider the issues of   developing localised infrastructure and technological solutions that increase the efficiency of   supply chains, meet specific market needs and provide a  competitive advantage in   the  еastern markets. Logframe and comparative analysis, systems approach, and modelling have been used in   the research process. As a   result, the study has identified a  number of  challenges for LNG producers, primarily related to   geopolitical complexities, regulatory environment, and market development dynamics, to   innovations, ecological norms, and understanding regional tensions that may impact supply chains and trade agreements. The findings of  the article can be   used when domestic companies develop strategies to  enter the  еastern LNG markets with existing contracts or  expand them.